Experiments on wall pressure at an area ratio 4.84 in a suddenly expanded flow field at supersonic Mach numbers - Khan, Sher Afghan; Chaudhary, Zakir Ilahi; Baig, Maughal Ahmed Ali; Ridwan, R; Chethan, K.M.; Faheem, Mohammed (AIP, 2022)
The present investigation intends to review the flow control mechanism’s effectiveness through a circular orifice of 1 mm diameter generating sonic flow at the exit even though experiments were conducted for various NPRs and a fixed level of expansion. Tests were conducted at Mach 1.87 for correct and under-expanded cases; for Mach 2.2, investigations were done at design NPR and over-expanded conditions. Lastly, for Mach 2.58, the study was over-expanded alone as the design NPR is 19.3. However, the research focuses on correctly, over, and under-expanded cases. When nozzles face adverse pressure, the control increases the pressure; when the nozzle flow is either ideally expanded or operating at NPR more than the design NPR, the control results in a decrease in pressure. The bare lowest duct size needed for the stream to stay connected is 1D for Mach 1.87 and 2D for the leftover two Mach numbers. Oscillations are observed for pipe size 6D and above, whereas, for short duct length, such fluctuations are not seen.